Lisez "Pour une paix durable, pour une démocratie populaire!"
Tessellated illustrations of newspaper front-pages carrying same headline as poster with circular photo montage of people across France and colonies smiling Poster advertising periodical published in 11 languages by the Information Centre of the Communist and Workers' Parties PO-0793